Evaluasi Pengelolaan Instalasi Pengolahan Air Limbah Puskesmas - Susanti, Amy Risqina; Wardoyo, Iva Rustanti Eri; Ngadino, Ngadino; Rokhmalia, Fitri (Politeknik Kesehatan Tanjung Karang, 2020)
Community health centers are releasing infectious wastewater that must be treated using a Wastewater Treatment Plant (WWTP). The performance of WWTP will affect the quality of effluent wastewater, while the quality has been determined by the Governor of East Java Regulation No. 72 of 2013, so as not to pollute the environment. This research purposed to evaluate the management of WWTP incommunity health center in Surabaya, which covers the north, south, east and west.Â This research analyzed the installation of 5 wastewater treatment plants, consisting of 2 WWTP Non-Inpatient Health Centers with the highest population category, and 3 Inpatient Health Centers with the highest number of beds. Data collection was obtained from observations, interviews and laboratory tests. Wastewater samplings were carried out at the inlet, after filtration and outlet. Data were analyzed descriptively and compared with East Java Governor Regulation No. 72 of 2013 and WWTP Technical Guidelines. The results of the research showed that the effluent quality of the Surabaya City Health Center wastewater treatment plant has met the quality standards. The discharge of wastewater community health centersnot exceed the maximum discharge of wastewater, but the Tanah Kalikedinding and the Jagir Health Center produced wastewater exceeding the discharge capacity of WWTP, so that the performances becomes less efficient. In terms of management, onlyÂ Dr. Soetomo health center had sufficient grades, while others got excellent grades.